Comportamento de aterro experimental sobre solo mole tratado com colunas de brita - Pires, Liliana Gonçalves Simões (2017)
This work will present the execution of an embankment on stone columns as the alternative chosen for soil ground treatment in a soft soil region. In order to evaluate the behavior of the foundation and the embankment of this region, which is designed to be the Sewage Treatment Plant in São Gonçalo - RJ, a smaller area with the greatest thickness of soft soil was selected. This area was named: test-landfill, which is the main objective of this study. This experimental area was monitored with piezometers and settling plates since the beginning of the execution of the compacted landfill. This thesis presents a description of the execution sequence of this embankment and the results of the geotechnical investigation made for the soil of this region. To evaluate the data obtained from the instrumentation, a series of methods of analysis were used: analytical, numerical and performance prediction methods, which are all presented in a calculation sequence format. This work will present and discuss values obtained for settlement, improvement factor and stabilization time. All of these values were obtained through analytical methods and compared with the results seen in the field from instrumentation.